Peningkatan kemampuan pemecahan masalah matematik melalui pembelajaran pendidikan matematika realistik untuk peserta didik SMP Negeri di Kabupaten Garut - Witri Nur Anisa (Program Studi Pendidikan Matematika, FKIP, Universitas Siliwangi, Tasikmalaya, 2015)
This research was aimed at analyzing the enhancement of students’ ability in mathematical problem solving through realistic mathematics education instruction, and at describing their attitude during realistic mathematic education instruction. The population is all junior high school students in Garut region. The experimental design used in this research was two-group design with pretest-posttest. The samples were the seventh grade students of SMP Negeri 3 Cilawu taken randomily and consisted of two classes (the grade of VII A and grade VII C) for the experimental group who participated in intruction with realistic mathematics education and other two classes (the grade of VII B and grade VII D) for the control group who participated in the direct instruction. Data collection tecniques used were Test and Questionnaires. The statistical analysis used was gain score for the test results of mathematical problem solving ability. The analysis results, showed that the enhancement of students’ mathematical problem solving ability who participated in intruction with realistic mathematics education was better than those who participated the direct instruction. Realistic mathematics education instruction has also given opportunities for students to have positive attitudes toward mathematics.